The central mediating effect of inhibitory control and negative emotion on the relationship between bullying victimization and social network site addiction in adolescents - Wang, Jiale; Wang, Ning; Qi, Tianci; Liu, Yang; Guo, Zhenhua (Frontiers in Psychology, 2025)
Background and objectivesBullying victimization is strongly associated with social network site addiction among adolescents. However, the underlying mechanisms between these variables remain unclear. This study aims to explore the psychological mechanisms linking bullying victimization to social network site addiction by examining the mediating roles of depression, anxiety, stress, and inhibitory control.MethodsA self-report survey was conducted among a sample of 1,005 adolescents in China. The survey included measures of bullying victimization, social network site addiction, depression, anxiety, stress, and inhibitory control. Descriptive and correlational analyses were performed, followed by the construction of a chain mediation model.ResultsBullying victimization was significantly positively associated with social network site addiction. However, this relationship became non-significant when negative emotional states (depression, anxiety, stress) and inhibitory control were introduced as mediating variables. Specifically, bullying victimization significantly predicted negative emotional states and was negatively associated with inhibitory control. Negative emotional states were also negatively related to inhibitory control, while inhibitory control was negatively associated with social network site addiction. Among the negative emotional states, stress and anxiety showed a significant negative correlation with social network site addiction.ConclusionThis study sheds further light on the psychological mechanisms linking bullying victimization and social network site addiction among adolescents. Depression, anxiety, stress, and inhibitory control act as mediating factors in this relationship. These findings highlight the importance of targeting these variables in understanding and developing interventions for social network site addiction among adolescents.